Ant Router: An efficient routing protocol for social opportunistic networks using ant routing. Issue 2 (1st March 2020) - Sharma, Deepak Kr.; Singh, Swati; Gautam, Vishakha; Kumaram, Shubham; Sharma, Mehul; Pant, Shrid
Abstract : Social opportunistic networks are a subclass of opportunistic networks which rely upon the predictability and established patterns of human social behaviour to facilitate the sharing of information by performing message routing. While the forwarding step purely depends upon the movement paradigm of nodes in the network, the said movement makes the network unreliable due to frequent disconnections and delay, and spasmodically connected environment. Various protocols have been developed so far for routing in such networks, whose primary aim is to ensure efficient and reliable message delivery. This study proposes a heuristic‐based scheme for routing messages from the source to the destination using the Ant Algorithm. Problems related to frequent disconnections and inefficient routing are overcome in the proposed protocol through features such as pheromones. This protocol is thoroughly examined via simulation and analysis to assess the performance with other routing protocols in social opportunistic networks under various parameters. The performance criterion for the comparisons includes overhead ratio, average residual energy, average latency, number of dead nodes and average buffer time. The examinations have shown that the authors algorithm is superior to protocols such as Prophet, Epidemic and ProWait on the basis of average latency and buffer time.